1994
DOI: 10.2307/2077911
|View full text |Cite
|
Sign up to set email alerts
|

Oligopolistic Interdependence and the Structure of Production in Banking: An Empirical Evaluation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 8 publications
2
44
0
1
Order By: Relevance
“…Fuentes and Sartre (1998) found that in the regional market of Spain, the level of competition was weak following consolidation thus lending support to the traditional view. Also Berg and Kim (1994) observed that for the Norwegian banking industry the conjectural variation is greater than one, implying that the industry is near monopoly with high degree of market power.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Fuentes and Sartre (1998) found that in the regional market of Spain, the level of competition was weak following consolidation thus lending support to the traditional view. Also Berg and Kim (1994) observed that for the Norwegian banking industry the conjectural variation is greater than one, implying that the industry is near monopoly with high degree of market power.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Where is the estimate of average price of bank production in country i which is proxy by the ratio of bank total revenue to total assets (Berg and Kim, 1994;Berger et al, 2009;Carb´o et al, 2009;Fern´andez and Gonz´alez, 2005;Shaffer, 2004). To estimate , the first derivative of translog cost function 3 with respect to is computed.…”
Section: Model Specificationmentioning
confidence: 99%
“…The average prices are estimated over total assets (TA) along the lines of Shaffer (1993) and Berg and Kim (1994) …”
Section: The Modelmentioning
confidence: 99%